Состояние и перспективы развития современных информационных технологий в медицине - Высоцкая, Е. В. (ХНУРЭ, 2008)
In the given work is considered the State of modem information technologies in medicine. There are certain perspective directions of its development, which will allow promate the level of medical service to high-quality in medical establishments.
Keywords: информационные технологии в медицине; information technologies in medicine